Respon pertumbuhan dan produksi kacang tanah (Arachis hypogaea L.) lokal kebar terhadap perlakuan pupuk kotoran kambing dan ukuran benih - Meage, Marthina; Wospakrik, Andrean H.; Sarungallo, Amelia S.; Rumainum, Inna Martha (Agrotek, 2023)
This study aims to determine the response of peanut gowth and production of local variety Kebar to goat manure treatment and peanut seed size. The method used was an experiment with a factorial randomized block design with two treatments. The first treatment was fertilizer dosage with 3 levels and the second treatment was seed size with 2 levels. Three levels for fertilizer doses, namely P0: 0 g/polybag; P1: 150 g/polybag, P2: 300 g/polybag. Two levels for seed size, namely, B1: small seed size (0.5 g) and B2: large seed size (0.8 g). The data was then analyzed using analysis of variation (Anova). If the treatment shows results that have a real effect, then continue with the DMRT further test. The results showed that the P2B2 treatment showed a higher leaf number and plant weight than the other treatments. However, the application of goat manure and seed size had no effect on number of pods, pod weight per plant, number of filled pods and 50 seed weight.